[tex]\mathbf X=\begin{bmatrix}-\dfrac43&-5\\\\-2&-\dfrac14\end{bmatrix}[/tex]
[tex]\mathbf Y=\begin{bmatrix}-\dfrac23&6\\\\4&-\dfrac34\end{bmatrix}[/tex]
[tex]\mathbf Y+\mathbf X=\begin{bmatrix}-\dfrac23-\dfrac43&6-5\\\\4-2&-\dfrac34-\dfrac14\end{bmatrix}=\begin{bmatrix}-2&1\\2&-1\end{bmatrix}[/tex]
[tex]4(\mathbf Y+\mathbf X)=\begin{bmatrix}4(-2)&4(1)\\4(2)&4(-1)\end{bmatrix}=\begin{bmatrix}-8&4\\8&-4\end{bmatrix}[/tex]
- - -
[tex]\mathbf M=\begin{bmatrix}2&-1\\-3&0\\5&2\end{bmatrix}[/tex]
[tex]\mathbf N=\begin{bmatrix}1&-4&7\\3&-1&1\end{bmatrix}[/tex]
[tex]\mathbf{MN}=\begin{bmatrix}2(1)+(-1)(3)&2(-4)+(-1)(-1)&2(7)+(-1)(1)\\-3(1)+0(3)&-3(-4)+0(-1)&-3(7)+0(1)\\5(1)+2(3)&5(-4)+2(-1)&5(7)+2(1)\end{bmatrix}=\begin{bmatrix}-1&-7&13\\-3&12&-21\\11&-22&37\end{bmatrix}[/tex]